The Relationship Between Mothers' Knowledge and Attitudes Towards Stunting Prevention Practices in Toddlers - Wiradi Suryanegara (International Journal of Health Engineering and Technology, 2025)
Stunting is a chronic nutritional problem and continues to be a significant public health challenge in Indonesia, including in the Bogor region. Mothers play a crucial role in preventing stunting through adequate knowledge, positive attitudes, and appropriate practices in nutrition and parenting. This study aimed to analyze the relationship between maternal knowledge and attitudes with stunting prevention practices at the North Bogor Health Center in March 2025. This study applied a cross-sectional design with a quantitative approach. A total of 60 mothers of toddlers were selected using a non-random accidental sampling technique. Data were collected through a validated questionnaire, using a Guttman scale for knowledge and a Likert scale for attitudes and practices. Analysis was performed using univariate and bivariate methods, with Fisher exact test and Chi-square test. The results indicated that most mothers had good knowledge (75%), positive attitudes (68.3%), and good practices (65%) in stunting prevention. A significant association was found between maternal knowledge (p = 0.036; OR = 5.125) and attitudes (p < 0.001; OR = 8.938) with prevention practices. In conclusion, maternal knowledge and attitudes are significantly related to stunting prevention. Strengthening maternal education and health promotion is essential to reduce stunting prevalence.